Upaya Meningkatkan Keberhasilan UMKM yang Dikelola Oleh Wanita melalui Variabel Kontekstual - Novie Noordiana Rachma Yulia; Wilsna Rupilu (RELASI : JURNAL EKONOMI, 2020)
Poverty and unemployment have become a problem in several developing countries, including Indonesia. One of the roles of SMEs in supporting the Indonesian economy is to reduce poverty through providing employment. Women's participation in the business sector has also increased, this phenomenon occurs throughout the world, including in Indonesia, as shown by USAID and IFC in the Market Research Study in 2016. This study aims to determine whether the factors in the form of access to capital, government support , social networking, competitive advantage and strategic market position, consumer orientation, business plans, marketing communications, and women's personality influence the success of women-owned SMEs, with the hope that this can be a motivation for Indonesian women for becoming more productive and having an entrepreneurial spirit. Data was taken from 400 respondents in 8 sub-districts in Surabaya, then processed using SPSS program. The results of this study showed that simultaneously the independent variables consist of Access to capital, Government Support, Social Networks, Competitive Advantages and Positioning, Consumer Orientation, Business Plans, Marketing Communications, and Women's strengths have a significant influence on the success of women-owned SMEs. While the results of the t test showed that partially the Social Network with an observation t value of 2.546, Business Plan with an observation t value of 4, 797, and finally the Advantages of Women with an observation t value of 8.768 affected the success of women-owned SMEs.